The Role of Deadwood in the Carbon Cycle: Implications for Models, Forest Management, and Future Climates - Wijas, Baptiste J. (2024)
Deadwood represents a significant carbon pool and unique biodiversity reservoir in forests and savannas but has been largely overlooked until recently. Storage and release of carbon from deadwood is controlled by interacting decomposition drivers including biotic consumers (animals and microbes) and abiotic factors (water, fire, sunlight, and freeze–thaw). Although previous research has focused mainly on forests, we synthesize deadwood studies across diverse ecosystems with woody vegetation. As changing climates and land-use practices alter the landscape, we expect accelerating but variable rates of inputs and outputs from deadwood pools. Currently, Earth system models implicitly represent only microbial consumers as drivers of wood decomposition; we show that many other factors influence deadwood pools. Forest management practices increasingly recognize deadwood as an important contributor to forest dynamics, biodiversity, and carbon budgets. Together, emerging knowledge from modeling and management suggests a growing need for additional research on deadwood contributions to carbon storage and greenhouse gas emissions.